Ultrasonic Irradiation: Synthesis, Characterization, and Preliminary Antimicrobial Activity of Novel Series of 4,6-Disubstituted-1,3,5-triazine Containing Hydrazone Derivatives - Hessa H. Al-Rasheed; Monirah Al Alshaikh; Jamal M. Khaled; Naiyf S. Alharbi; Ayman El-Faham (Journal of Chemistry)
Novel series of 4,6-disubstituted-1,3,5-triazines containing hydrazone derivatives were synthesized employing ultrasonic irradiation and conventional heating. The ultrasonication gave the target products in higher yields and purity in shorter reaction time compared with the conventional method. IR, NMR (H 1 and C 13), elemental analysis, and LC-MS confirmed the structures of the new products. The antimicrobial and antifungal activities were evaluated for all the prepared compounds against some selected Gram-positive and Gram-negative bacterial strains. The results showed that only two compounds 7i (pyridine derivative) and 7k (4-chlorobenzaldehyde derivative) displayed biological activity against some Gram-positive and Gram-negative bacteria, while the rest of the tested compounds did not display any antifungal activity.